Polymorphism identification of Diacylglycerol Acyltransferase1 gene and its correlation with fat content of Saanen goat - Darmoatmodjo, L. M. Y. D.; Widodo, W.; Asmara, W. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
Gene markers are often usefull for selection process of cattle on commercial certain phenotypes. Saanen goat has predominance in milk production traits. Milk fat content is one of the commercial traits of milk production. Diacylglycerol Acyltransferase1 (DGAT1) gene was involved in the final process of triglyceride synthesis and associated with milk fat content. Single nucleotide subtitution or insertion-deletion in certain sequence of DGAT1 gene could be gene markers for milk fat content. The objective of this study was to identify differences variation in milk fat content among individual Saanen goats, to identify exon 14-16 polymorphism of DGAT1 gene and to examine its correlation between polymorphism and milk fat content on Saanen goats. The methodologies was collection blood and milk samples, DNA isolation from blood, amplification of DGAT1 genes, sequencing, detection of polymorphism of exon 14-16 DGAT1 gene with Polymerase Chain Reaction-Single Strand Conformation Polymorphism (PCR-SSCP), and examination milk quality on three lactation months using Lactoscan. The average of daily milk production from 70 Saanen goat was 2340±709 mL, 1880±632 mL, 1432±536 mL and average of milk fat content was 3.07±0.52%, 2.53±0.55%, 3.00±0.55% for the first, second and third months of lactation, respectively. The amplicon size of exon 14-16 of DGAT1 gene was ± 350 bp and showed monomorphic pattern from PCR-SSCP. Variation of milk fat content on Saanen goats not caused by polymorphism of exon 14-16 DGAT1 gene.